Strategies to improve the early detection and management of ectopic pregnancies in primary care - Alharbi, Shada Murshed; Mazi, Orjuwan Abdulbari; Aljassar, Marah Rashed; Al-Omani, Danah Jazaa; Alharbi, Lama Yousef; Rasheed, Yasmen Tawfeeq; Alhagbani, Mona Abdulrahman; Alyami, Maram Mohammed; Gadeer, Rana Hassan; Alsenan, Yasmeen Zaki; Ibrahim, Nuha Eltigani (International Journal Of Community Medicine And Public Health, 2023)
Even in the advanced era of today, maternal morbidity and mortality are quite high; however, most pregnancy-related complications can be successfully prevented by early diagnosis and timely management. The primary care setting is of utmost importance in this regard, as it is the first line of contact between patients and physicians, and regular antenatal care services are provided by most of primary care settings. Ectopic pregnancy is one of the most prevalent pregnancy disorders and is further associated with high-risk complications and mortality. The clinical manifestations may mimic non-ectopic pregnancy conditions, making it difficult to develop diagnostic standards. However, ultrasonography and human chorionic gonadotropin (β-hCG) levels can ensure early diagnosis. Conservative treatment is pursued since surgical management is linked to multiple significant side effects. In most situations, pharmacotherapy using methotrexate in a single- or multi-dose regimen is the preferred course of treatment. Performing ultrasonography as soon as a pregnancy is confirmed to determine the location of the pregnancy, monitoring β-hCG levels, and ensuring prompt referral in the event of a possible ectopic pregnancy that cannot be treated conservatively are all important ways that primary care settings can play a significant role in early diagnosis and prompt management. Additionally, obstetric ultrasonography training for family physicians can help in the early detection of ectopic pregnancy, which can lead to favourable results. The purpose of this research is to review the available information about strategies to improve the diagnosis and management of ectopic pregnancy in primary care.